STUDI EKOLINGUISTIK DALAM DINAMIKA TUTUR BAHASA JAWA RAGAM PERTANIAN PADA MASYARAKAT BUDDHA DI DUSUN GUNUNG KELIR KULON PROGO - Danang Try Purnomo (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2020)
This study raised about the treasures of Javanese agricultural lexicon in the dynamics of Buddhist community speech in Gunung Kelir village Kulon Progo district. The purpose of this research is to describe the shape and meaning of the agricultural lexicon in the dynamics of Javanese speech of Buddhist society and its relevance to the implications of ecological changes in the dynamics of Javanese speech in the region. This type of research is qualitative research. The form of research is descriptive with ecolinguistic approach. The result of this study is, first, the acquisition of lexicon in the form of glue in the form of words and phrases. Second, the resulting lexicon refers to several classifications, namely the lexicon related to the workings of agriculture, the lexicon related to the materials and agricultural equipment, the lexicon related to agricultural products, the animal-related lexicon, and the lexicon related to environmental conditions. Third, the existence of the use of Javanese language of agricultural variety represents a relatively maintained environmental sustainability. This is influenced by the dependency of people who still depend on life through agriculture. However, the potential for threat of various agricultural speech still exists because of the devolution of the farming profession to the next generation that tends to decrease and the influence of population growth and technological advances that help shift the function of land